Odpowiedzi

2009-11-18T13:53:00+01:00
3x+2y=5/*(-1)
2x+2y=2

-3x-2y=-5 dodajemy stronami
2x+2y=2

-x=-3/*(-1)
x=3
podstawiamy x do 1 równania
3*3+2y=5
2y=5-9
2y=-4//2
y=-2
1 3 1
2009-11-18T13:56:28+01:00
/3x+2y=5
\2x+2y=2 /*(-1)

/3x+2y=5
+ \-2x - 2y = -2 (odejmujemy dolne od górnego)
------------------------
x = 3
3*3 +2y = 5 ( za x podstawiamy 3)
9 +2y = 5
2y = 5-9
2y =- 4
y = -2

x = 3
y =-2
==================================================

/2x-11y=73 /*3
\ 3x-4y=47 \* (-2)

/6x - 33y = 219
\-6x + 8y = -94
---------------------------
-25y = 125
y = -5
3x - 4*(-5)=47 (za y podstawiamy -5)
3x = 47-20
3x = 27
x = 9

x = 9
y =-5



1 5 1
  • Użytkownik Zadane
2009-11-18T13:56:27+01:00
A)
3x+2y=5 /×-1
2x+2y=2

-3x-2y=-5
2x+2y=2
------------------(sumujemy)
-x=-3 /×-1
x=3

2×3+2y=2 /:2
3+y=1
y=1-3
y=-2

b)
2x-11y=73 /×3
3x-4y=47 /×-2

6x-33y=219
-6x+8y=-94
------------------(sumujemy)
-25y=125 /:-25
y=-5

-6x+8y=-94 /:2
-3x+8×-5=-47
-3x-40=-47
-3x=-47+40
-3x=-7 /:-3
x=3/7
1 3 1